Internal Factors Inhibiting Entrepreneurship in Beauty Vocational High School Alumni - Tree Rahayu; Merita Yanita (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
This study aimed to determine the internal factors inhibiting entrepreneurship of alumni of SMKN 3 Payakumbuh, Department of Beauty Management. This type of research is quantitative research with descriptive methods. The population in this study was alumni of SMK Negeri 3 Payakumbuh majoring in beauty management graduates from 2017-2018 as many as 86 people with a sample of 43 people. The data in this study used primary data and secondary data. The questionnaire used was the Likert Scale. Data processing is carried out using a Statistical Product Solution and Service (SPSS) program with steps to determine the frequency distribution and determine the percentage rate. The results of this study are internal factors in inhibiting the entrepreneurship of alumni of SMKN 3 Payakumbuh who graduated in 2017 and 2018, gaining a percentage of 56% with the Medium category. This means that alumni of SMKN 3 Payakumbuh who graduated in 2017 and 2018 consisting of 43 respondents have a moderate category of internal factors in inhibiting entrepreneurship. So it is recommended that the Beauty Management department pay more attention to the learning process in entrepreneurship subjects.